Prostate-specific membrane antigen (PSMA) expression in primary and metastatic renal cell cancer (UroCCR-65 study) - Salma Binzaqr; David Kryza; Anne-Laure Giraudet; Jean Christophe Bernhard; Marine Gross-Goupil; Mokrane Yacoub; Gaelle Margue; Elif Hindié; Clément Morgat (EJNMMI Research)
Abstract Background Prostate-specific membrane antigen (PSMA) has been shown to be overexpressed in the neo-vasculature of renal cancers. However, studies investigating the pattern of PSMA expression in primary RCC and RCC metastases according to metastatic sites are rare. 44 frozen samples of RCC, 19 primaries (9 clear cell (cc) RCC, 7 papillary (pap) RCC, and 3 chromophobe (ch) RCC) and 25 (24 samples have ccRCC histology and one is unclassified) unpaired metastases (8 from adrenals, 8 from bones, 2 from lungs, 2 from liver and 5 others (1 lymph node, 1 pancreas, 1 brain, 1 gallbladder and 1 muscle)), were available from the UroCCR project (NCT03293563). PSMA expression was assessed by autoradiography using [177Lu]Lu-PSMA-617 as binding agent and the specific binding (total binding—non-specific binding) was calculated and expressed as a percentage of total binding. A patient suffering from metastatic ccRCC was also administered [68Ga]Ga-PSMA-11 to evaluate PSMA expression. Results The mean specific binding was 28.9 ± 40.4% for primary renal cancer and 65.0 ± 38.9% for metastasis. Regarding histology, high PSMA expression was depicted in 33.3% of ccRCC, 33.3% of chRCC and 57.1% of papRCC. PSMA was more frequently expressed in primary samples of papRCC histology with renal capsule invasion (p = 0.0286). A higher PSMA-specific binding and a higher number of samples with high PSMA-expression were depicted in metastatic samples. Bone metastasis showed lower binding than other metastatic sites combined (p = 0.0005). The patient suffering from metastatic ccRCC showed high [68Ga]Ga-PSMA-11 uptake on known distant metastases and additional site uncovered. Conclusion PSMA showed high expression in metastases of ccRCC. Clinical trial registration NCT, NCT03293563, prospectively registered September 20, 2017, http://www.clinicaltrials.gov .